Pattern of specific dermatoses of pregnancy: a hospital based study - ., R. Indradevi; ., P. Oudeacoumar; Besra, Laxman; ., V. Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The specific dermatoses of pregnanc represent a heterogenous group of ill-defined pruritic skin diseases related specifically to pregnancy and/or the immediate postpartum period. The objective of the study is to determine the patterns of specific dermatoses of pregnancy in a tertiary care hospital. Methods: A total of 450 pregnant females, irrespective of their parity and gestational age were screened for various pruritic skin conditions and those with specific pregnancy dermatoses were identified and evaluated. Results: The age of the study population ranged from 18 to 36 years (mean age 24 years). The study population included 261 (58%) primigravidae and 189 (42%) multigravidae. Seventeen (3.77%) pregnant females had specific dermatoses of pregnancy. Out of these, 9 (52.94%) had pruritic urticarial papules and plaques of pregnancy (PUPPP), followed by pruritic folliculitis of pregnancy in 5 (29.41%), pruritic gravidarum in 2 (11.76%) and pemphigoid gestationis in 1 (5.88%). PUPPP was the commonest specific dermatoses noted in our study. Conclusions: The present study highlights the pattern of specific dermatoses of pregnancy in our hospital. Early diagnosis of specific dermatoses of pregnancy may prevent harmful effect on mother and fetus. The pruritic eruptions of pregnancy, which are not a rare entity can be a source of significant distress to the pregnant female and need timely therapeutic intervention.